A STUDY ON PRODUCTION PROFILE IN QUAILS FED WITH PROBIOTICS - L. RAM SINGH, K. VENKATA RAMANA, ASHOK KUMAR DEVARASET E. SUNIL ANAND KUMAR and (The Journal of Research, PJTSAU, 2017)
The objective of this study was to investigate the effect of supplementation of Dietary baker’s yeast as a probiotic on body performance of Japanese quails (Coturnix coturnix japonica). In this experiment a total of 96 day-old unsexed, growing Japanese quails were equally divided into three groups of 32 birds in each group. The experiment was terminated when birdswere 6 weeks old. The standard basal diet was fed in first group (G1), 5% and 10% level of baker’s yeast was supplemented in basal diet for second group (G2) and third group (G3) respectively. Feed and water was supplied ad libitum for all the birds. Body performance was determined by measuring feed intake, body weight gain and feed conversion ration. The results obtained in this study showed that, supplementation of dietary baker’s yeast had positive effect on production performance in Japanese quails